Description of Ecdyonurus solus sp. nov., a new species of the Ecdyonurus venosus species-group (Ephemeroptera: Heptageniidae) from the Crimean Peninsula, Ukraine - Kłonowska-Olejnik, Małgorzata; Prokopov, Grigorii A.; Godunko, Roman J. (Zootaxa, 2007)
The larvae and adults of Ecdyonurus solus sp. nov., are described and illustrated. This species is found in the mountainous region of the Crimean Peninsula, and belongs to the Ecdyonurus venosus species-group. SEM photographs of the eggs of new species are presented. The distinguishing characteristics separating this E. solus sp. nov. from closely related species of the E. venosus species-group are discussed. Detailed data on the biology and distribution of the new species are presented.